Aquecimento vocal para o canto erudito: teoria e prática - Lopes de Araujo, Andre Luiz; Momensohn dos Santos, Teresa Maria; Pinto Giannini, Susana Pimentel; Miguel, Fabio [UNESP]; Petian, Andrea (Univ Federal Goias, 2014)
Vocal warm-ups are essential for the technical training of the singer, for good speech and performance, as well as essential for good vocal health and a long-lasting career. Objective: To analyze the theory and practice of the vocal warm-up in classical singing, from the perspective of different professionals in the voice field including: teachers, speech therapists and singers. Method: descriptive search, quantitative in nature, cross-sectional, with a questionnaire for voice teachers, singers and audiologists. The sample consisted of 165 subjects: 86 voice teachers, 64 speech pathologists, and 15 singers. Results: Teachers of Singing (97.7 %), singers (95.3 %) and students (93.3 %) use the vocal warm-up. Conclusion: From the results we can infer that most of the professionals surveyed point to the importance of the implementation of the vocal warm-up before a performance, and the strategy used by most voice instructors, speech therapists and singers is vocalization, i.e. aesthetic warm-up.

A realização do aquecimento vocal se torna essencial no processo de formação técnico do cantor, para uma boa fonação e performance, indispensável para uma boa saúde vocal e longa carreira profissional. Objetivo: Analisar a teoria e a prática sobre o aquecimento vocal no canto erudito, a partir da ótica de diferentes profissionais da área da voz: professores de canto, cantores e fonoaudiólogos. Método: Pesquisa de caráter descritivo, de natureza quantitativa, de corte transversal, com aplicação de um questionário para professores de canto, cantores e fonoaudiólogos. A amostra foi composta por 165 sujeitos: 86 professores de canto, 64 cantores e 15 fonoaudiólogos. Resultados: Professores de canto (97,7%), cantores (95,3%) e fonoaudiólogos (93,3%) utilizam o aquecimento estético. Conclusão: a partir dos resultados desta pesquisa pode se inferir que a maioria dos profissionais pesquisados apontam a importância da realização do aquecimento vocal antes de uma performance, e a estratégia mais utilizada para realizar o aquecimento vocal pela maioria dos professores de canto, fonoaudiólogos e cantores é o vocalise, ou seja, aquecimento estético.
Vocal warm-up in classical singing: theory and practical application
Keywords: Vocal warm-up; Singing; Voice; Music; Aquecimento vocal; Canto; Voz; Música